2014
DOI: 10.3389/fnhum.2014.00719
|View full text |Cite
|
Sign up to set email alerts
|

Motoneuron firing in amyotrophic lateral sclerosis (ALS)

Abstract: Amyotrophic lateral sclerosis is an inexorably progressive neurodegenerative disorder involving the classical motor system and the frontal effector brain, causing muscular weakness and atrophy, with variable upper motor neuron signs and often an associated fronto-temporal dementia. The physiological disturbance consequent on the motor system degeneration is beginning to be well understood. In this review we describe aspects of the motor cortical, neuronal, and lower motor neuron dysfunction. We show how studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 174 publications
(225 reference statements)
1
27
0
1
Order By: Relevance
“…However, it is very important to highlight that, besides MN and NMJ properties, strong evidence indicates that alterations are also present at several other levels of the motor circuit in ALS (reviewed in de Carvalho et al . ).…”
Section: Als‐related Electrophysiological Changes In Mns and Nmjsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it is very important to highlight that, besides MN and NMJ properties, strong evidence indicates that alterations are also present at several other levels of the motor circuit in ALS (reviewed in de Carvalho et al . ).…”
Section: Als‐related Electrophysiological Changes In Mns and Nmjsmentioning
confidence: 97%
“…This could provide insight into how the relationship of MN excitability and NMJ synaptic dysfunctions relates to the vulnerability of the lower motor circuit in ALS. However, it is very important to highlight that, besides MN and NMJ properties, strong evidence indicates that alterations are also present at several other levels of the motor circuit in ALS (reviewed in de Carvalho et al 2014).…”
Section: Alsmentioning
confidence: 99%
“…by vibratory excitation of 1a afferents, is sufficient to increase the RMP beyond threshold by causing a reduced net outward current flow insufficient to maintain the normal RMP. A brief excitation can then cause rhythmic, repeated firing . Baldissera et al .…”
Section: Neurophysiology Of Crampmentioning
confidence: 99%
“…by vibratory excitation of 1a afferents, is sufficient to increase the RMP beyond threshold by causing a reduced net outward current flow insufficient to maintain the normal RMP. A brief excitation can then cause rhythmic, repeated firing [30]. Baldissera et al [28,32] suggested that cramp could be arrested by the combined effect of afferent activity in group Ia and II activity and of pain fibre activation, leading to blockade of the H reflex response pathway and silencing of the continuous motoneuronal discharge (Fig.…”
Section: Neurophysiology Of Crampmentioning
confidence: 99%
“…Muscle wasting and weakness in motoneuron diseases arise predominantly from the loss of motoneurons. Hence, research has focused on investigating the mechanisms of motoneuron cell death (de Carvalho et al, 2014). In addition, there is growing evidence indicating that alterations of NMJs and/or the skeletal muscle itself affect the pathogenic process in amyotrophic lateral sclerosis (ALS) (Miller et al, 2006;Murray et al, 2010;Wong and Martin, 2010).…”
Section: Introductionmentioning
confidence: 99%